Influence of Al2O3 diffusion barrier and PbTiO3 seed layer on microstructural and ferroelectric characteristics of PZT thin films by sol-gel spin coating method - Kim, SH; Kim, CE; Oh, YJ (ELSEVIER SCIENCE SA, 1997)
Sol-gel spun-casted Pb(Zr0.52Ti0.48)O-3 [PZT] thin film with Al2O3 buffer layer and PbTiO3 seed layer was successfully prepared at a low temperature of 550 degrees C. Al2O3 buffer layer, as a diffusion barrier between the silicon substrate and the Pt bottom electrode, suppressed interface reactions between the film and the substrate and prevented the interdiffusion of Pb and Si elements. PbTiO3 seed layer between the Pt bottom electrode and the PZT thin film promoted the formation of perovskite phase at lower temperature due to the presence of ample nucleation sites. The microstructure of the PZT thin film is composed of homogeneous submicron grains. Dielectric constant and tan delta of the PZT thin film with the buffer and the seed layer were enhanced by 3-5 times in comparison to the PZT film wthout the buffer and the seed layer. Typical P-E hysteresis behavior was observed even at applied voltages as low as 5 V, manifesting greatly improved remanent polarization and coercive field. Fatigue characteristic, measured at 7 V, showed stable behavior. Degradation in polarization was found to be less than 5% at 10(8) cycles. (C) 1997 Published by Elsevier Science S.A.
Keywords: ZIRCONATE-TITANATE FILMS